New Stability Indicating Ultrafast Liquid Chromatographic Method for the Determination of Sofosbuvir in Tablets - Annapurna, Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: To develop a new sensitive, precise, simple, and economic stability indicating reverse phaseultrafast liquid chromatographic (RP-UFLC) method for the estimation of Sofosbuvir (SFB) in bulk and its tablet dosage forms. Materials and Methods: Chromatographic separation was achieved through C8 Phenomenex column (250 mm × 4.6 mm i.d., 5 μm particle size) using acetonitrile: 0.1% Formic acid mixture as the mobile phase. The Shimadzu model CBM-20A/20 Elite high-performance liquid chromatography system was monitored at detection wavelength 259 nm in isocratic mode with flow rate 0.8mL/min and the total run time is 10 min. The method was validated, and forced degradation studies were conducted. Results and Discussion: SFB has obeyed Beer-Lambert’s law over a concentration range 1–200 μg/ mL with correlation coefficient 0.9998. The limit of detection and limit of quantification are found to be 0.2541 μg/ mL and 0.7642 μg/mL, respectively. The percentage relative standard deviation in precision and accuracy studies was found to be <2% and the percentage recovery is 98.11–98.78%. SFB was found to be highly sensitive toward alkaline conditions. Conclusions: It is observed that this RP-UFLC method is accurate, precise, sensitive, and reproducible for the estimation of SFB in tablets. The method was validated as per the ICH guidelines and very much specific as the degradants were well separated without interfering the drug peak.